Menelusuri Labirin Peran Perempuan Dalam Pelayanan Gereja Yang Patriarki - Astrid Natasya; Hikman Sirait; Meriyana (Sekolah Tinggi Teologi Ekumene Jakarta., 2024)
The role of women in church ministry has been a long topic, especially in the context of churches that still adhere to patriarchal structures. The patriarchal church still places women in certain tasks that are considered